PROBLEMS PLAGUING THE INDIAN AVIATION INDUSTRY - Dhir, Tanya (2016)
The research investigates the various issues inhibiting the prospective growth of aviation in the Indian skies. To highlight this, a historical context has been revisited in the literature review. To capture different dimensions of the investigation, triangulation has been conducted by converging data from primary research (telephonic interviews), secondary research and theoretical literature. The analysis has revealed certain key impediments ranging from inferior infrastructure, inflated fuel prices, stiff competition with the railways, insufficient training universities, scanty tourism, to red-tapism. In addition to these external factors, flawed strategies, mismanagement, deadwood, suicidal predatory pricing, debt traps, substandard service and low reliability are some areas that need to be addressed immediately on the airline’s front. After assimilating these problem areas, an attempt has been made to propose certain strategies in order to propel Indian aviation to its potential.